On pseudo null and null cartan darboux helices in minkowski 3-space - Öztürk, Ufuk; Nešović, Emilija (Kuwait Journal of Science, 2016)
In this paper, we introduce the notion of pseudo null and null Cartan Darboux helicesin Minkowski 3-space. We characterize the Darboux vectors of the pseudo null andthe null Cartan curves in terms of the Darboux helices and the rectifying curves. Wefind an explicit parameter equation of a pseudo null curve of constant precession andprove that there are no null Cartan curves of constant precession. Finally, we givesome examples.